Ethnicity, gender and higher education. Trajectories of two Arhuaco women in Colombia (2016)
Two main questions are addressed in this text: how have these indigenous feminine leaders faced cultural restrictions to meet the demands of public life? How have they created a diverse amalgam of capital and knowledge as part of their leadership? The main theoretical elements used in this work are: The sociological perspective and field theory of Bourdieu, studies on intersectionality by Lorde (1984) and Pratt-Clarke (2010), the studies on higher education of Gil (2005), Choque (2015) and Mato (2015), and finally, the feminine leadership studies of Lumby and Coleman (2007). Our methodological approach is the reconstruction of two scholarly and professional personal trajectories from an intersectional perspective.